The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0187550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uric acid-lowering therapy in patients with chronic kidney disease: A meta-analysis

Abstract: Background and objectivesThe effects of uric acid-lowering therapy in patients with chronic kidney disease (CKD) remain uncertain. Therefore, we undertook a systematic review and meta-analysis to investigate the effects of uric acid-lowering agents on major clinical outcomes of CKD.Design, setting, participants, and measurementsAccording to the pre-specified protocol that was registered with PROSPERO (No. CRD42016038030), we searched systematically in MEDLINE, EMBASE, and the Cochrane Library for trials up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 51 publications
4
67
0
7
Order By: Relevance
“…Accordingly, the indication for plasma UA‐lowering therapy, with either xanthine‐oxidase inhibitors or uricosuric agents, may be broader than that for gout or UA nephrolithiasis. Interestingly, in studies in diverse populations including type 2 diabetes mellitus (T2DM) patients, plasma UA‐lowering therapy improved surrogate cardio‐renal end points, although dedicated large‐sized trials, such as the ongoing ALL‐HEART study (ISRCTN32017426), are needed to firmly establish causation between UA lowering and long‐term clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the indication for plasma UA‐lowering therapy, with either xanthine‐oxidase inhibitors or uricosuric agents, may be broader than that for gout or UA nephrolithiasis. Interestingly, in studies in diverse populations including type 2 diabetes mellitus (T2DM) patients, plasma UA‐lowering therapy improved surrogate cardio‐renal end points, although dedicated large‐sized trials, such as the ongoing ALL‐HEART study (ISRCTN32017426), are needed to firmly establish causation between UA lowering and long‐term clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in studies in diverse populations including type 2 diabetes mellitus (T2DM) patients, 4,[9][10][11] plasma UA-lowering therapy improved surrogate cardio-renal end points, although dedicated large-sized trials, such as the ongoing ALL-HEART study (ISRCTN32017426), are needed to firmly establish causation between UA lowering and long-term clinical outcomes. 4 Over the last 3 decades, multiple antihyperglycaemic drug classes, with different modes of action, have been successfully licensed for the treatment of hyperglycaemia in T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that investigate whether UAlowering therapy is effective for cardiorenal protection partly answers the question because they provides an insight about the causal relationship between increased UA levels and CV diseases. Indeed, a substantial number of reviews and 1 3 meta-analysis that were recently conducted has shown that UA-lowering therapies retard the progression of cardiorenal disease, thereby leading to a better prognosis [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…включили в метаанализ наиболее значимые на тот момент времени работы, вы-Обзор полненные с целью оценки эффекта разных уратснижающих терапий (в 15 исследованиях назначали ингибиторы ксантиноксидазы аллопуринол или фебуксостат, в одном -препарат пегуриказы пеглотиказа) при ХБП. Полученные результаты позволили констатировать снижение ОР развития почечной недостаточности более чем в 1,5 раза, сердечно-сосудистых катастроф на 60% и расчетной СКФ на 4,10 мл/ мин/1,73 м 2 в год [23]. Наиболее показательными были результаты исследования, проведенного M. Goicoechea и соавт.…”
Section: гиперурикемия как фактор риска развития патологии почек и пеunclassified